2015
DOI: 10.3109/13880209.2014.980585
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofPiper nigrumextracts: Restorative perspectives of high-fat diet-induced changes on lipid profile, body composition, and hormones in Sprague–Dawley rats

Abstract: PnL extracts significantly reduced the body weight, fat%, and ameliorated HFD-induced hyperlipidemia and its constituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
7
23
0
Order By: Relevance
“…28 Obesity and associated metabolic consequences induce changes that promote apoptosis and atrophy of skeletal muscles. These animals showed significantly increased blood glucose, insulin total cholesterol, triglycerides and calculated HOMA-IR as noted by Sishi et al 4 and Parim et al 30 One of the most important organs responsible for glucose uptake, disposal, and storage is skeletal muscles, which account for about 75% of the whole body's glucose uptake under insulin stimulation. 29 The current study showed that rats fed with HFD for 16 weeks gained more body weight and visceral fat when compared with chow fed group.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…28 Obesity and associated metabolic consequences induce changes that promote apoptosis and atrophy of skeletal muscles. These animals showed significantly increased blood glucose, insulin total cholesterol, triglycerides and calculated HOMA-IR as noted by Sishi et al 4 and Parim et al 30 One of the most important organs responsible for glucose uptake, disposal, and storage is skeletal muscles, which account for about 75% of the whole body's glucose uptake under insulin stimulation. 29 The current study showed that rats fed with HFD for 16 weeks gained more body weight and visceral fat when compared with chow fed group.…”
Section: Discussionsupporting
confidence: 69%
“…29 The current study showed that rats fed with HFD for 16 weeks gained more body weight and visceral fat when compared with chow fed group. These animals showed significantly increased blood glucose, insulin total cholesterol, triglycerides and calculated HOMA-IR as noted by Sishi et al 4 and Parim et al 30 One of the most important organs responsible for glucose uptake, disposal, and storage is skeletal muscles, which account for about 75% of the whole body's glucose uptake under insulin stimulation. 31 Different mechanisms are involved in skeletal muscle's insulin resistance encountered in cases of obesity; impaired skeletal muscle microvascular responses to insulin, 32 oxidative stress caused by obesity that impairs glucose uptake low-grade inflammation and decreased IRS-1 activation.…”
Section: Discussionsupporting
confidence: 69%
“…extracts have shown effect in reducing the body weight, fat, ameliorated high fat diet-induced hyperlipidemia and its constituents. 23 Ginger and pepper have shown to modulate oxidative stress caused by hypercholesterolemia. 24 Ginger has demonstrated decrease in all lipid profile parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Diet induced obesity in animals revealed the relationship between obesity and poor bone quality, as resolute by suppressed micro architectural and biomechanical properties. [ 29 ] Extreme obesity has been shown to have negative impact on bone health, which is associated with profound increase in the levels of obesity-related factors like TNF-α and IL-6. [ 30 31 32 ] In the present study, the elevated level of TNF-α was observed in HFD induced obese rats.…”
Section: Discussionmentioning
confidence: 99%